Cover Jurnal Fitopatologi Vol. 18 No. 6, November 2022 - Editors Jurnal Fitopatologi Indonesia (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2022)
This editorial contains the front cover, editorial page, and back cover of the Jurnal Fitopatologi Indonesia Vol. 18 No. 6, November 2022